Peningkatan Nilai Ekonomi Melalui Pemanfaatan Limbah Rumah Tangga di Kelurahan Lion Tondok Iring - Dwibin Kannapadang; Rati Pundissing; Chrismesi Pagiu; Dian Intan Tangkeallo; Samuel Randy Tapparan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This community service aims to increase economic value through the utilization of household waste in Tondok Iring Village, Makale Utara District, Tana Toraja Regency. This activity was carried out by a team of lecturers from the Management Study Program, Faculty of Economics, UKI Toraja. The processing of household waste by applying 3 (three) principles namely reduce (reduce), reuse (reuse) and recycle (recycle). The basis of this activity is so that the people of Tondok iring village can process and utilize household waste into a creative product with economic value. As for the specific uses for the people of Tondok Iring village, they better understand how to utilize household waste such as making from recycled materials used cans. used plastic jars, used plastic bottles, and used plastic cups into money storage (piggy banks), places to store stationery, and as flower vases. The target of this activity is aimed at the community of Tondok Iring Village to increase economic value by utilizing household waste.